Inclusão social: estudo sobre trabalho e deficiência física na região metropolitana de João Pessoa. - Spinelli, Maria Filomena Nobrega (2007)
Handicapped people social inclusion possibility through the work bias has constituted itself in a subject too much actual because of the globalization process and the consequent changes deriving from this process in relation to the job market and employment. This way, the present study had as an objective to analyze how the insertion process of persons with physical deficiency occurs in the formal job market in João Pessoa metropolitan area, with base in the legal guaranties that support these subjects. For that, it was developed a research of qualitative basis, having the Fundação Centro Integrado de Apoio ao Portador de Deficiência (FUNAD) as the process mediator agent in six companies, with 18 (eighteen) persons with physical deficiency, 9 (nine) related to the Human Resources Sector of each participant company and 5 (five) responsible for the company admission selection process. The instruments for data collection were a half-structured interview and documental analysis, being thoroughly submitted to critical analysis. The realized data pointed to the identification of a person with physical deficiency profile in the job market, that corresponds to young individuals, with slight deficiencies, receiving low wages, but without demonstrating dissatisfaction, that reveals the existence of comprehension difficulties, on the part of the companies, about the inclusion process, denouncing the need of employing just to accomplish quotes and not to contribute to the persons with physical deficiency laboring potentiality recognition.